THE STUDY OF THE RELATIONSHIP BETWEEN GENERAL SUCCESS, MATHEMATICAL SUCCESS, ATTITUDE TO MATHEMATICS AND MATHEMATICAL THINKING IN ELEMENTARY STUDENTS - Alijonov Sirojiddin Husan o'g'li (American Journals, 2025)
This article fifth grade latest teaching of governors of the overall achievement, mathematics achievement, mathematics attitude and mathematical thinking between the complex connection of the net to learn. Scientific research and empirical evidence relied on without, in this research, these factors mutually influence and readers of academic effectiveness and mathematics into a relationship in formation to each other how effects that learns. This the main variables between the relationship of the study, through teachers and politicians’ mathematics education students of the success of stimulating effective strategies about valuable in understanding possible they may.
Keywords: General achievement, mathematics achievement, mathematics into the relationship, mathematical thinking, fifth grade students, academic achievement, mathematics education.